ANALISIS PENGGUNAAN CRAM FLASHCARDS TERHADAP PRESTASI BELAJAR PESERTA DIDIK SEKOLAH DASAR PADA PEMBELAJARAN SAINS - Rispen Elfandi Lase; Yemima Destri Telaumbanua; Fortin Wan Boi Gea; Edward Harefa (Jurnal Tunas Pendidikan, 2023)
Many previous studies have shown that learning motivation and learning effectiveness can be enhanced through educational learning media, and the recent introduction of enriched game elements has made such interactive games increasingly popular. The main objective of this study was to help primary school learners learn science-related concepts by participating in an educational card game, Cram flashcards. The researcher then investigated learners' perceptions regarding the integration of the game into science learning as well as the educational benefits of the game in relation to learning performance. A one-group pretest-post test design was implemented with 94 elementary school learners in Gunungsitoli City, North Sumatra, selected through purposive sampling. The results of this study found that the learners showed a positive attitude towards the use of educational card games in science learning. The results also showed the effectiveness of the proposed educational card game in improving science knowledge on transportation and energy. The study also suggests that teachers can explore learners' attitudes towards learning using card games to identify the elements that arouse interest and how knowledge is acquired through this interactive learning medium.